Serum levels of neutrophil gelatinase-associated lipocalin, kidney injury molecule-1, and cystatin-C in renal artery stenosis: A pilot study - Raghunandan Prasad; Reeta Choudhary; Anuradha Singh; Surabhi Agarwal; P Kaushik; Kritika Singh; Rajanikant R Yadav; Amar Singh Yadav; Dharmendra Singh Bhadauria; Hira Lal (Indian Journal of Rheumatology)
Background: The present pilot study evaluated the potential of newer renal biomarkers (neutrophil gelatinase-associated lipocalin [NGAL], cystatin-C [Cys-c], and kidney injury molecule-1 [KIM-1]) in estimating subclinical renal injury due to renal artery stenosis (RAS). Materials and Methods: A total of 13 patients of magnetic resonance angiography confirmed RAS and 14 normotensive healthy controls were enrolled in the study after obtaining ethics approval and informed consent. Serum was collected from participants to check for serum levels of NGAL, KIM-1, and Cys-c by quantitative enzyme immunoassay. The data of RAS patients were compared and analyzed against the data of healthy controls. Results: sNGAL, sKIM-1, and sCys-c values in RAS patients showed rising trend as compared to normal healthy control; however, the difference in their values was not statistically significant. This could be due to small and heterogeneous sample size. However, statistically significant difference was noted in the values of sNGAL and sCys-c between healthy controls and RAS patients with abnormal serum creatinine. This difference in the values of these biomarkers was also statistically significant between RAS patients with normal and elevated serum creatinine. Conclusion: In RAS patients, sNGAL, sCys-c, and sKIM-1 seem to have potential as an early biomarker of kidney injury.